Homeownership schemes in Malaysia for first homebuyers - Tan, Teck-Hong * (2013)
Home ownership is beneficial not only to households but also to communities as a whole. However, there is little evidence to inform discussion of meeting housing needs of first-time homebuyers in conditions of rapid urbanisation. One way to address their housing needs and preferences is to understand the housing attributes required by them to own a house. In order to achieve sustainability in housing delivery system, affordable housing schemes must be economically viable, socially acceptable and technically feasible.